Dynamic system linear models and Bayes classifier for time series classification in promoting sustainabilitys - Abdulsattar Abdullah Hamad; Faris Maher Ahmed; Mamoon Fattah Khalf; M. Lellis Thivagar (Heritage and Sustainable Development, 2023)
Research purpose: The current work introduces a novel method for time series discriminant analysis (DA). Proposing a version for the Bayes classifier employing Dynamic Linear Models, which we denote by BCDLM This article explores the application of DLMs and the Bayes Classifier in time series classification to promote application in sustainability across diverse sectors.